2001
DOI: 10.1091/mbc.12.4.847
|View full text |Cite
|
Sign up to set email alerts
|

RAC1 Regulates Adherens Junctions through Endocytosis of E-Cadherin

Abstract: The establishment of cadherin-dependent cell-cell contacts in human epidermal keratinocytes are known to be regulated by the Rac1 small GTP-binding protein, although the mechanisms by which Rac1 participates in the assembly or disruption of cell-cell adhesion are not well understood. In this study we utilized green fluorescent protein (GFP)-tagged Rac1 expression vectors to examine the subcellular distribution of Rac1 and its effects on E-cadherin-mediated cell-cell adhesion. Microinjection of keratinocytes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
150
3
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(172 citation statements)
references
References 46 publications
16
150
3
3
Order By: Relevance
“…3g,h), indicating that RhoA promotes both CME and CIE. On the other hand, Rac1 expression affected only the uptake of dextran (Fig. 3g,h), suggesting that Rac1 regulates CIE but not CME, consistent with previous observations 34,35 . We examined the molecular hierarchy among RhoA, Rac1 and Ras.…”
Section: Article Nature Communications | Doi: 101038/ncomms3763supporting
confidence: 91%
“…3g,h), indicating that RhoA promotes both CME and CIE. On the other hand, Rac1 expression affected only the uptake of dextran (Fig. 3g,h), suggesting that Rac1 regulates CIE but not CME, consistent with previous observations 34,35 . We examined the molecular hierarchy among RhoA, Rac1 and Ras.…”
Section: Article Nature Communications | Doi: 101038/ncomms3763supporting
confidence: 91%
“…M-cadherin ubiquitination and endocytosis in RhoAV14-expressing cells might result from its failure to associate with p120 catenin (Figure 10). Indeed, endocytosis has emerged as a regulatory mechanism that modulates cadherin cell surface levels in cells (Le et al, 1999;Akhtar and Hotchin, 2001;Palacios et al, 2002), and recent reports have shown that p120 catenin controls VE-cadherin internalization and degradation (Xiao et al, 2003). Thus, p120 is a regulator of cell-cell adhesion through the maintenance of cadherin levels in cells (Ireton et al, 2002;Davis et al, 2003;Peifer and Yap, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, integrinactivated focal adhesion kinase (FAK) can phosphorylate β-catenin and thus induce its ubiquitylation and degradation and the disassembly of the E-cadherin cell adhesion complex [59]. Endocytosis of E-cadherin can occur via clathrin or caveolin-dependent mechanisms [60][61][62]. A key player in clathrin-mediated E-cadherin endocytosis is Arf6, a Ras-related small GTPase.…”
Section: Transcriptional Control Of E-cadherinmentioning
confidence: 99%